Digestibility of cod liver oil in the diet of Labeo rohita fingerlings - Sethuramalingam, T A; Haniffa, M A (Indian Journal of Fisheries, 2011)
The effect of inclusion level and adaptation time on the apparent digestibility ofcod liver oil (CLO) in Labeo rohita fingerlings was determined. Cod liver oil wasincluded into a casein based reference diet at 10, 12.5 and 15% inclusion levelswith chromic oxide (1%) as an external indicator. Digestibility analyses was doneon faeces pooled over 3 sets of 5 successive days (1-5 day; 10 -15 day; 21-25 dayrespectively) and unpooled daily faecal samples. The apparent digestibility coefficient(ADC) decreased significantly from 85 to 57% as the CLO was increasedfrom 10 to 15% in the diet. The digestibility of gross e n e i ^ of CLO decreasedsignificantly from 78.4 to 36% as the inclusion level was increased from 10 to15%. But the protein digestibility offish was not affected by CLO inclusion in thediet. The analyses on the digestibility of pooled and unpooled samples of faecesrevealed that L. rohita require more time to adapt to maximum digestibility athigher inclusion levels of CLO in the diet. Results indicated the necessity todetermine the ADC of CLO over the range of inclusion levels to be used and alsothe importance to ensure complete adaptation of the feed to obtain maximumdigestibility results.